Sediment erosion of head cover pressure balancing pipe-A Case study of Chameliya hydroelectric power station - Acharya, Chiranjibi; Poudel, Laxman; Bhattrai, Sudip (Journal of Innovations in Engineering Education, 2022)
The majority of rivers in the Himalayan basins have considerable concentrations of hard minerals (minerals with hardness greater than that of turbine material) in their sediment. Generally, the concentration is minimum during the dry season and maximum during the wet season. These particles pass through the turbines of run-off-river hydroelectric power plants and cause their parts to erode and deteriorate. This deterioration causes frequent unit shutdowns for maintenance and repair, particularly during the wet season resulting in inconsistency in the generation of electrical power. In the case of the Francis turbine, one of the parts suffering from sediment-led erosion is the head cover and its pressure balancing pipe. The Chameliya Hydropower Plant (CHEPS), located in the Darchula district of Far-Western Province in Nepal has been used as a case study in this study to investigate the erosion caused by sediment in the head cover pressure balancing pipe. Sediment erosion in the balancing pipe has been a significant issue for CHEPS ever since it was commissioned. It is thus vital to foresee the erosion-prone locations in the balancing pipe in order to minimize the erosion thereby minimizing such losses. Analyses of erosion have been done by a field study at CHEPS and Computational Fluid Dynamics (CFD) based erosion modeling using a commercial CFD code ANSYS Fluent. The ANSYS Fluent solver uses the Cell Centered Finite Volume Method (FVM) for the solution of the governing equation Results obtained from field setting research at CHEPS and computational simulations are then compared qualitatively and quantitatively. In the field study, eroded elbows were examined for erosion patterns, and one elbow's wall thickness was measured by cutting it into four lengthwise quarters. Additionally, the sediment concentration (ppm) in the inflowing water was tested by sampling the flow (incoming to the turbine) on various dates during the rainy season (i.e. from May 3, 2021, to August 2, 2021). The average concentration was found to be 2718.39 ppm, with the maximum concentration being 5308.70 ppm on July 4 and the minimum being 420.20 ppm on May 3. Particle Size Distribution (PSD) and mineral content of sediment samples collected in February 2022 (a dry month), August 2021(monsoon month) and June to August 2022 (monsoon month) were examined. According to PSD analysis, 90% of the particles (by weight) fall in the range of 0.01 mm to 0.1 mm in the dry month and in the range of 0.01 mm to 0.5 mm in the wet month. Despite weather variations, the mineral composition of the silt was seen to be stable, with an average of 70.8% of the minerals being harder than the material of the pressure balance pipe (i.e. cast steel). The principal hard minerals identified thus far include quartz, feldspar, garnet, and tourmaline. Elbow wall thickness loss due to erosion was measured, and the erosion rate density at respective points was calculated. Using the average sediment concentration during the rainy season (2718.39 ppm) and the average particle size of 0.2 mm, erosion rate density was also calculated at the same locations using CFD simulation. The location of the erosion-prone area was the same as the real-life scenario, and the erosion rate density from the simulation follows the same trend as the experimental value with an deviation (average error) of 69.58%.